Diagnosis and Management of Central Serous Chorioretinopathy - Ammar Fardhana; AK Ansyori; Ramzi Amin (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2020)
Introduction: Abnormalities in the macula is a very significant disorder. One abnormality that can be found is central serous chorioretinopathy (CSC). This case report aims to explain the diagnosis and management of Central Serous Chorioretinopathy. Case presentation: A 32-year-old man, a soldier, came for treatment at hospital on May 2017. Anamnesis of major complaints right eye blurred since, 1 week before hospitalization. From the investigations, in the right eye, the armsler grid examination showed an impression of metamorphopsia. On examination of the fundus photo, an impression of macular area edema with a clear border is obtained. OCT examination revealed that there was elevation of neuroretina tissue in the macula. This patient was managed by laser photocoagulation at the point of leakage of subretinal fluid. Conclusion: The diagnosis of central serous chorioretinopathy is made through history taking, ophthalmological examination, and supporting examinations of armsler grid, photo fundus, OCT and FFA. Laser photocoagulation can be performed, especially in cases of persistent, chronic, recurrent, or occupational needs.